HUKUMAN MATI DAN PENERAPAN SANKSI HUDUD DI INDONESIA DAN NEGARA-NEGARA MAYORITAS MUSLIM PERSPEKTIF HAK ASASI MANUSIA - orien, orien effendi (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
This article explains why there is a controversy over the application of the death penalty in Indonesia and also the application of hudud in Muslim-majority countries. Opponents argue that the application of the death penalty and hudud sanctions is contrary to the principles of human rights, while others argue that the application of the death penalty as a deterrent and the application of hudud witnesses is a command of Islamic teachings. Therefore, this article explains the rationale of these two arguments by exploring various sources and facts. In conclusion, those who support believe that the death penalty can provide a deterrent effect, they consider that the abolition of the death penalty will make things worse, while the reason for maintaining hudud sanctions departs from the view of conservatism, namely static and textual thinking in applying the teachings of Islamic law, they argue that Islamic teachings sourced from the Al-Qur'an and Al-Hadith are very sacred, so hudud sanctions must be applied. Meanwhile, those who reject the progressive view demand the fulfillment of the right to life and the right to be treated humanely for lawbreakers